Modern Social and Cultural Anthropology (II) - Gendrolis, Edmundas (Problemos, 1977)
The article deals with the main trends of neo-evolutionism. The revival of the concept of evolutionism in cultural and social anthropology is of particularistic character. Typical in this respect is the theory of multilinear evolution put forward by J. Steward, and the theoretical views of E. E. Evans-Pritchard, M. Gluckman and others. L. White and his followers are more consistent concerning the principle of historicism. Discontent with the traditional methods of investigation of pre-class societies finds expression in the works of bourgeois anthropologists who refer more and more frequently to the theory of Marxism. While acknowledging the scientific value of some of the conceptions of Marxism, they reject its main methodological conclusions and the theory of social revolution in particular.